(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
Golden ponyfish Photopectoralis aureus and Goldstripe ponyfish Karalla daura are small fish with less economic value. Many marine fish population parameters were not investigated because of their low commercial value. Therefore, the primary goals of this study were to determine the size frequency, length-weight relationship (LWR), length-length relationship (LLR), and Fulton’s condition factor (Kn) of two tropical ponyfishes from Saint Martin’s Island. From March to April 2022, specimens were caught using fixed purse nets. A total of 409 specimens of P. aureus and K. daura were measured to determine size frequency, LWRs, LLRs, and Fulton’s condition factor. For P. aureus, the maximum total length (TL) of 12.9 cm sets a new record. The LWRs for P. aureus and K. daura were highly significant (p<0.001), where the coefficient of determination (r2) was 0.985 and 0.869 for P. aureus and K. daura, respectively. The estimated slope (b) for P. aureus and K. daura were 3.147 and 2.986, respectively. The LLR equations were TL = 1.1089 SL + 0.2689 for P. aureus and TL = 0.6792 SL + 3.3309 for K. daura. The Kn value had no significant difference between the species of different length classes for P. aureus (0.97-1.40) and K. daura (1.19-1.26). There has never been any prior reporting of LWRs or length-length relationships (LLRs) for P. aureus in literature or FishBase. The study’s findings may benefit the management and conservation of these ponyfishes. Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 105-114